Characterization of SAT2 foot‐and‐mouth disease 2013/2014 outbreak viruses at the wildlife–livestock interface in South Africa. Issue 4 (12th February 2020) - Blignaut, Belinda; van Heerden, Juanita; Reininghaus, Björn; Fosgate, Geoffrey T.; Heath, Livio
Abstract: The Southern African Territories (SAT)‐type foot‐and‐mouth disease viruses (FMDV) are endemic to the greater Kruger National Park (KNP) area in South Africa, where they are maintained through persistent infections in African buffalo. The occurrence of FMDV within the Greater KNP area constitutes a continual threat to the livestock industry. To expand on knowledge of FMDV diversity, the genetic and antigenic relatedness of SAT2‐type viruses isolated from cattle during a FMD outbreak in Mpumalanga Province in 2013 and 2014 were investigated. Cattle from twelve diptanks tested positive on polymerase chain reaction (PCR), and molecular epidemiological relationships of the viruses were determined by VP1 sequencing. Phylogenetic analysis of the SAT2 viruses from the FMD outbreak in Mpumalanga in 2013/2014 revealed their genetic relatedness to other SAT2 isolates from topotype I (South Africa, Zimbabwe and Mozambique), albeit genetically distinct from previous South African outbreak viruses (2011 and 2012) from the same topotype. The fifteen SAT2 field isolates clustered into a novel genotype with ≥98.7% nucleotide identity. High neutralization antibody titres were observed for four 2013/2014 outbreak viruses tested against the SAT2 reference antisera representative of viruses isolated from cattle and buffalo from South Africa (topotype I) and Zimbabwe (topotype II). Comparison of the antigenic relationship (r1 values) of the outbreak viruses with reference antisera indicated a good vaccine match with 90% of r1 values > 0.3. The r1 values for the 2013/2014 outbreak viruses were 0.4 and above for the three South African vaccine/reference strains. These results confirm the presence of genetic and antigenic variability in SAT2 viruses and suggest the emergence of new variants at the wildlife–livestock interface in South Africa. Continuous characterization of field viruses should be performed to identify new virus strains as epidemiological surveillance to improve vaccination efforts.